2019
DOI: 10.1111/dom.13686
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of pemafibrate in people with type 2 diabetes and elevated triglyceride levels: 52‐week data from the PROVIDE study

Abstract: The aim of this study was to evaluate the efficacy and safety of pemafibrate in people with type 2 diabetes and hypertriglyceridaemia over a 52‐week period. Participants were randomly assigned to receive treatment with placebo or pemafibrate at a dose of 0.2 or 0.4 mg/d for 24 weeks (treatment period 1). The main results from treatment period 1 have been reported previously. The assigned treatment was continued up to week 52, except that the placebo was changed to pemafibrate 0.2 mg/d after week 24 (treatment … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
29
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(31 citation statements)
references
References 15 publications
2
29
0
Order By: Relevance
“…Its higher efficacy over fenofibrate has been confirmed by several clinical trials in Japan [ 155 158 ]. The safety profile of pemafibrate has shown no clinically adverse effects on renal or hepatic function [ 157 , 159 ], and it is well tolerated over 52 weeks in T2D patients with hypertriglyceridemia [ 159 ], and in patients with impaired kidney function [ 160 ]. Importantly, pemafibrate does not show any drug interactions with various statins as demonstrated in two clinical studies [ 161 ].…”
Section: Current Therapeutic Options Related To Pparα For Treating DCmentioning
confidence: 99%
“…Its higher efficacy over fenofibrate has been confirmed by several clinical trials in Japan [ 155 158 ]. The safety profile of pemafibrate has shown no clinically adverse effects on renal or hepatic function [ 157 , 159 ], and it is well tolerated over 52 weeks in T2D patients with hypertriglyceridemia [ 159 ], and in patients with impaired kidney function [ 160 ]. Importantly, pemafibrate does not show any drug interactions with various statins as demonstrated in two clinical studies [ 161 ].…”
Section: Current Therapeutic Options Related To Pparα For Treating DCmentioning
confidence: 99%
“…Pemafibrate was approved in Japan 2017 for the treatment of dyslipidemia [28,29,30,31,32,33,34,35,36,37,38]. A phase II study showed that 0.05–0.4 mg/day pemafibrate significantly reduced plasma TG levels (−30.9% to −42.7%) and increased HDL-C levels (11.9% to 21.0%) [29].…”
Section: Pemafibrate As a Novel Spparmαmentioning
confidence: 99%
“…In LDL receptor knockout mice, pemafibrate decreased apoC3 expression and increased plasma LPL activity suggesting increased clearance capacity (79). Similarly, Araki et al observed decreased plasma apoC3 in patients with T2D treated with pemafibrate (77). These studies suggest that pemafibrate could effectively modulate CM production to treat diabetic dyslipidemia.…”
Section: Effects Of Currently Approved Lipid Modifying and Antidiabetmentioning
confidence: 88%